Brazilian “holy” spring waters - Lazzerini, Fábio Tadeu (2014)
http://dx.doi.org/10.5902/2179460X13707The water sources related to beliefs, rituals, mythical powers or dressings can induce the sustainable development and its protection recommended through increased knowledge to support this action. Beyond the fundamental importance to the environment, the holy waters, miracle or healing springs have close correlation with the human origin, history, tradition, health, religion, science and economy. In Brazil, comparatively to its great water potential, there are little recognized locations of sacredness and pilgrimage, where occurs the waters influence on the formation and ritualization of indigenous beliefs, traditional societies, African and Catholics religions and their mixtures. This paper prospected and evaluated social, physical-chemical and salutogenic aspects of springs or fountains called “divine” in 102 Brazilian cities. In several occurrences, some biologically active components of therapeutic potential have been identified, in addition to legal requirements for obtaining the classification of mineral waters. The communities identified possess tradition with thermalism in spas or with attractive health and religious tourism. The healing miracle has not been explained, but the fact has been considered as sacred and belonging to our natural and cultural patrimony.